GAMBARAN HASIL PEMERIKSAAN pH, ERITROSIT DAN BENDA KETON PADA URINE YANG DITUNDA PEMERIKSAANNYA SELAMA 2 JAM DAN 3 JAM MENGGUNAKAN METODE CARIK CELUP DI UPF. BKTM MAKASSAR - Muh. Rizman Naim (Bajang Institute, 2024)
The kidneys are one of the main organs in the urinary system or urinary tract system whose function is very important in maintaining survival. The very important functions of the kidneys include: filtering blood, filtering and removing waste, monitoring and controlling water balance in the body, regulating blood pressure and salt levels in the blood, regulating red blood cells, regulating blood acid-base balance (pH), maintaining mineral and electrolyte concentrations (sodium, potassium, phosphorus, and calcium) and producing the active form of vitamin D. All electrolyte ions osmolality of extracellular fluids are excreted by the kidneys through urine. In general, the types of errors that affect laboratory results by any method can be broadly classified into 3 main categories, namely errors in the pre-analytical stage of 61%, the analytical stage of 25.1% and the post-analytical stage of 13.9%. Based on these data, the most errors occur in the pre-analytical stage. Pre-analytical errors occur before patient specimens are examined to determine their analytics using a particular method. In the pre-analytical process, one of the most important roles is sample handling, including procedures that must be carried out if laboratory examinations are postponed. The purpose of this study was to determine pH, urine erythrocytes and ketone bodies using the dipstick method on urine that was postponed for 2 hours and 3 hours at UPF. BKTM Makassar.The method in this study uses a quantitative approach with the type of research used in this is descriptive. The type of data used is primary data obtained by conducting laboratory tests and secondary data in the form of literature data, data from medical records of patients in the polyclinic, and documentation during the study. There were 30 respondents who were used as research samples with accidental sampling techniques. Based on the results of the study conducted from the Oneway ANOVA test on 30 respondents of pH examination, urine erythrocytes and ketone bodies in urine which were examined initially then postponed for 2 hours and 3 hours using the dipstick method, it can be concluded that the Significance value (Sig.) of the data on the pH examination is 1,000 which is greater than the α value of 0.05 or 1,000> 0.05 and it can be concluded that there is no significant difference. In the examination of Urine Erythrocytes it is 0.653 which is greater than the α value of 0.05 or 0.653 > 0.05 and it can be concluded that there is no significant difference. While in the examination of Ketone Bodies it is 1,000 which is greater than the α value of 0.05 or 1,000 > 0.05 and it can be concluded that there is no significant difference.